Nurses experience increased clinical and organisational competence by working with a medical quality register, RevNatus - a qualitative study - Hilde Bjørngaard; Hege Svean Koksvik; Bente Jakobsen; Kjersti Grønning (BMC, 2022)
Abstract Background RevNatus is a consent-based, nationwide medical quality register that collects data on patients with inflammatory rheumatic diseases during pregnancy and one year postpartum. The entering of data takes place in outpatient clinics in rheumatology wards in hospitals. The aim of this study is to explore how rheumatology nurses experience organizing and working with the medical quality register RevNatus in addition to their normal clinical patient-care tasks. Methods Qualitative focus group interviews and individual in-depth interviews were conducted in 2018 to gain insights into how nurses organize performing quality register work and clinical work simultaneously. Data were analysed using systematic text condensation. Results The informants represented seven different rheumatology outpatient clinics in Norway. The analyses showed that working with RevNatus increased the nurses' knowledge about pregnancy and rheumatic diseases, improved the content of their nurse consultations and found the 'register form' as a useful template to structure the nurse consultations. The nurses took the main responsibility for RevNatus, but lack of routines and uncoordinated collaboration with the rheumatologists and secretaries made the nurses spend too much time verifying the accuracy of data or post-registering missing data. Conclusion The nurses experienced work with RevNatus as time-consuming, but the register work increased both their clinical and organisational competences. Routines and collaboration within the registry team are important to ensure the data quality and reduce the workload.